Biomass production of tropical trees across space and time: The shifting roles of diameter growth and wood density - Hornink, Bruna (2025)
1. Woody biomass in tropical trees contributes significantly to global carbon stocks; however, these stocks are increasingly affected by climate and land-use changes. Understanding the growth mechanisms driving woody biomass production is essential for assessing the short- and long-term contributions to carbon stocks and dynamics in tropical forests. 2. Trees accumulate biomass by increasing their size (wood volume) and/or tissue density (wood density). However, estimates of tree biomass production are often based solely on size increment through measurements of stem diameter growth, overlooking the potential spatial and temporal variation in wood density within trees. Tree-ring analysis can be applied to reconstruct past tree volume-growth and wood-density variations, allowing the quantification of their relative contributions when reconstructing past woody biomass production. 3. Here, we studied trees of the widespread Neotropical genus Cedrela along an environmental (climate and soil) gradient to address two key questions: (1) How does temporal variation in tree diameter growth and wood density affect biomass production? (2) To what extent do these relationships vary along the environmental gradient? We examined both long-term (ontogenetic) and short-term (annual) variations in diameter growth and wood density, covering eighteen sites in the Amazon rainforest, Atlantic Forest, Cerrado savanna and Caatinga dry forest. 4. We found that diameter growth and wood density drive short- and long-term biomass production dynamics. Interestingly, diameter growth patterns predominantly explained short-term variability in biomass production at all sites, whereas wood density explained ontogenetic biomass patterns mainly at humid sites. These results highlight the importance of accounting for both short- and long-term variation, including climatic and ontogenetic drivers, to increase the accuracy of biomass estimations in tropical trees, particularly in humid forest ecosystems such as the Amazon. 5. Synthesis. Diameter growth is an important and good indicator of forest carbon production. However, size-related changes in wood density, which are usually neglected, are critical for accurate short- and long-term carbon assessments, especially in tropical humid sites.